2015
DOI: 10.3892/ol.2015.3780
|View full text |Cite
|
Sign up to set email alerts
|

Putative cancer-initiating stem cells in cell culture models for molecular subtypes of clinical breast cancer

Abstract: Abstract. Cancer-initiating stem cells (CISC) represent a minor subpopulation of heterogeneous breast cancer. CISC are responsible for the acquired resistance to conventional chemoendocrine therapy and eventual relapse observed in patients with breast cancer. Certain molecular subtypes of clinical breast cancer that exhibit differential expression of genes coding for hormone and growth factor receptors differ in their response to conventional chemoendocrine therapy and targeted therapeutic inhibitors. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…It occurs predominantly due to the emergence of drug-resistant stem cells (6,40,41). Data presented on the isolation and characterization of DOX-resistant triple negative MDA-MB-231 cells validate a potential model for stem cell-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It occurs predominantly due to the emergence of drug-resistant stem cells (6,40,41). Data presented on the isolation and characterization of DOX-resistant triple negative MDA-MB-231 cells validate a potential model for stem cell-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Human tissue-derived preclinical models may reduce extrapolation of evidence for clinically relevant translational potential (16,18,41). Current research directions have provided optimized human tissue-derived cell culture models for triple negative molecular subtype of clinical breast cancer that represent a clinically relevant experimental system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that drug-resistant cancer stem cells have been isolated and characterized from colon carcinoma-derived cell culture models (31)(32)(33) and from luminal A and triple-negative breast carcinoma-derived cell culture models (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that about 40% of BC patients have experienced recurrence, and about 60-70% of patients display distant metastasis (4). Like normal human organs, tumors have a small number of primitive stem cells that have high proliferation, self-renewal, and differentiation potential.…”
Section: Introductionmentioning
confidence: 99%